Improved Phase Corrections for Transoceanic Tsunami Data in Spatial and Temporal Source Estimation: Application to the 2011 Tohoku Earthquake. Issue 12 (13th December 2017) - Ho, Tung‐Cheng; Satake, Kenji; Watada, Shingo
Abstract: Systemic travel time delays of up to 15 min relative to the linear long waves for transoceanic tsunamis have been reported. A phase correction method, which converts the linear long waves into dispersive waves, was previously proposed to consider seawater compressibility, the elasticity of the Earth, and gravitational potential change associated with tsunami motion. In the present study, we improved this method by incorporating the effects of ocean density stratification, actual tsunami raypath, and actual bathymetry. The previously considered effects amounted to approximately 74% for correction of the travel time delay, while the ocean density stratification, actual raypath, and actual bathymetry, contributed to approximately 13%, 4%, and 9% on average, respectively. The improved phase correction method accounted for almost all the travel time delay at far‐field stations. We performed single and multiple time window inversions for the 2011 Tohoku tsunami using the far‐field data (>3 h travel time) to investigate the initial sea surface displacement. The inversion result from only far‐field data was similar to but smoother than that from near‐field data and all stations, including a large sea surface rise increasing toward the trench followed by a migration northward along the trench. For the forward simulation, our results showed good agreement between the observed and computed waveforms at both near‐field and far‐field tsunami gauges, as well as with satellite altimeter data. The present study demonstrates that the improved method provides a more accurate estimate for the waveform inversion and forward prediction of far‐field data. Key Points: The phase correction method is improved by adding the effects of ocean density stratification, actual raypath, and actual bathymetry The ocean density stratification effect has the largest additional contribution, and its inclusion leads to more accurate results The result of multiple time window inversion from far‐field stations is similar to that from near‐field and all stations